Elite Power and Development Politics: An Analysis of Local Power Structures and Social Change in Indonesia - Cinu, Surahman; Fina, Elfina; Mahyudin Syam, Dedi (Journal of Public Administration and Government, 2026)
Development is not only understood as a process of economic growth and physical infrastructure expansion, but also as a political and social process shaped by power relations among various actors within society. This article aims to analyze the structure of elite power in the dynamics of local development politics and its implications for development policy and social change in Indonesia. This study employs a qualitative approach with a descriptive analytical design through a literature review of various academic sources related to political elites, local power structures, and development politics. The analysis applies elite theory to explain how elite groups occupy dominant positions in public decision making processes and control the distribution of development resources. The findings indicate that local power structures are formed through interactions among political elites, government bureaucracy, economic actors, and community leaders who develop both formal and informal power networks, such as political patronage and patron client relationships. These conditions often lead to the phenomenon of elite capture, which can influence development policies and potentially reinforce social inequality. Therefore, more inclusive and participatory development policies are necessary to promote fair and sustainable social change in society